2004
DOI: 10.5194/acp-4-1025-2004
|View full text |Cite
|
Sign up to set email alerts
|

Gas-particle interactions above a Dutch heathland: III. Modelling the influence of the NH<sub>3</sub>-HNO<sub>3</sub>-NH<sub>4</sub>NO<sub>3</sub> equilibrium on size-segregated particle fluxes

Abstract: Abstract. Micrometeorological measurements of sizesegregated particle number fluxes above Dutch heathlands and forests have repeatedly shown simultaneous apparent emission of particles with a diameter (D p )<0.18 µm and deposition of larger particles when measured with optical particle counters. In order to assess whether this observation may be explained by the equilibrium reaction of ammonia (NH 3 ), nitric acid (HNO 3 ) and ammonium (NH + 4 ), a new numerical model is developed to predict the vertical conce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…However, due to the drying procedure in this study, the error due to hygroscopic growth was estimated to be below 10%. In addition to water vapor, semi-volatile organic and inorganic vapors may result in particle growth and shrinkage, leading to spurious number fluxes for fixed sizebins, as pointed out by Nemitz and Sutton (2004) and Nemitz et al (2009). Due to the very large uncertainty in particle growth rates in the Amazon Basin , these potential errors are harder to quantify, though.…”
Section: Flux Measurementsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, due to the drying procedure in this study, the error due to hygroscopic growth was estimated to be below 10%. In addition to water vapor, semi-volatile organic and inorganic vapors may result in particle growth and shrinkage, leading to spurious number fluxes for fixed sizebins, as pointed out by Nemitz and Sutton (2004) and Nemitz et al (2009). Due to the very large uncertainty in particle growth rates in the Amazon Basin , these potential errors are harder to quantify, though.…”
Section: Flux Measurementsmentioning
confidence: 94%
“…Several biogenic related elements (e.g. K, P, S, Zn) in plants are present in the fluids circulating in plants and can be released from the plant during transpiration (Nemeruyk, 1970). The latent heat flux is at maximum at 12:00 LT and is much lower at 15:00 LT (Fig.…”
Section: Diurnal Cycles Of Fluxes Of Particles With Diametersmentioning
confidence: 99%
“…3.1. Nemitz and Sutton (2004) modelled the effect of NH 4 NO 3 evaporation on the apparent deposition velocity and found that, for some scenarios, the evaporation can lead to apparent emission of small particles. In one scenario, false positive fluxes were seen for particles less than 300 nm at a height of 10 m. Here, we investigation the extent of false fluxes due to ammonium-nitrate evaporation.…”
Section: Ammonium-nitrate Evaporationmentioning
confidence: 99%
“…The equilibrium mass concentration of NH 4 NO 3 , M, is a function of temperature, T , and relative humidity, S R , as well as the concentrations of NH 4 NO 3 , NH 3 , and HNO 3 , (cf. Mozurekwich, 1993;Nemitz and Sutton, 2004). Assuming all aerosol particles contain some NH 4 NO 3 , the change in mass of particles (with diameter D) due to the evaporation or condensation of NH 4 NO 3 is…”
Section: Ammonium-nitrate Evaporationmentioning
confidence: 99%
“…Both short-and long-term NH 3 measurement studies have been undertaken in Europe over many years (e.g., Burkhardt et al, 1998;Horvath and Sutton, 1998;Sutton et al, 2001Sutton et al, , 2009Huber and Kreutzer, 2002), but long-term measurements in the U.S. have been limited. Due to the relatively rapid equilibration of NH 3 with ambient ammonium nitrate (NH 4 NO 3 ) aerosol (Meng and Seinfeld, 1996;Nemitz and Sutton, 2004), measurements of gaseous NH 3 alone are not sufficient to fully characterize its nature. To do so requires simultaneous measurements of both gas-phase NH 3 and particle-phase NH 4 + (predominately in the fine particle fraction), preferably at similar temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%